Cyberspace and the sacralization of information - O'Callaghan, Sean (2014)
The attempts by advocates of the Swedish piracy movement to create a religious grouping known as Kopimism, a new religion which takes as its main ideas the beliefs that all information is sacred and all information should be freely available, have opened up an important debate around the nature of information itself and the ways in which it can be conceived of as being sacralized: Information is holy, Code is law, Copying is sacrament, is the motto of the Kopimist movement, with cyberspace itself being viewed as a sacred space. There has been considerable debate around the validity of Kopimism as a religious entity and this paper explores the historical development of the movement, as well as the philosophical rationale behind what it claims to be its core beliefs.
Keywords: Cyberspace; cyberspirituality; Gnosticism; Information; Kopimism